The Influence of Gamification on Learning on the Affective Domain of Elementary School Students: Systematic Literature Review - Minsih; Aniatul Mualifah (Jurnal Inspirasi Pendidikan, 2024)
Gamification is the application of game elements in non-game contexts, has become an innovative trend in education to improve students' motivation, engagement, and learning experience. This study aims to systematically examine the effect of gamification on the affective domain of elementary school students, which includes aspects such as interest, attitude, and emotional values in learning. Using the Systematic Literature Review (SLR) approach based on the PRISMA method, this study analyzed relevant literature from leading databases. A total of 40 selected articles from leading journals, conferences, and literature were identified, involving empirical studies on the implementation of gamification in education. The results of the analysis showed that gamification consistently increased students' intrinsic motivation, emotional engagement, and positive attitudes towards learning. This study also found that the effect of gamification on the affective domain was greatly influenced by the implementation design, educational context, and teacher ability in utilizing technology. Thus, this study concludes that gamification has great potential to improve the affective aspect of learning at the elementary school level, but its success is highly dependent on proper design and implementation. This study recommends the development of a gamification model that is more inclusive and relevant to students' learning needs, as well as the integration of systematic evaluation elements to measure its long-term impact and make an important contribution to understanding the potential of gamification as a pedagogical approach that can improve the quality of learning, especially in the affective aspects of elementary school students.